SELF CARE MANAGEMENT EVALUATION IN HYPERTENSION PATIENTS - Raja Sihotang; Tuti Anggriani Utama; Titin Aprilatutini; Nova Yustisia (Jurnal Vokasi Keperawatan (JVK), 2020)
Hypertension is a health problem that needs attention because of its high morbidity and mortality. hypertension must be treated properly because it causes various kinds of complications. Compliance becomes a form of independence in the management of patients, especially those with hypertension, in the form of a framework that focuses on selfcare. The purpose of this study is to review the literature to determine the percentage of self care management of hypertensive patients. The literature search method was carried out through the CINAHL, DOAJ, and Pubmed database and obtained 30 research articles and then examined the completeness of the menus in the research articles with a total of 15 articles. After that, the criteria  and  stages of  critical  review were  carried out  using the  Joanna Briggs Institute (JBI) format with a total of 10 articles that were reviewed by literature. The results showed that hypertension self management was in the good category. Further research is needed to provide an intervention strategy for hypertensive patients to improve self-care practices and control of related factors.